Método da varredura de superfície como alternativa na investigação da interferência eletromagnética em drivers de led - Rodrigues, Igor Matheus Leal (2023)
In this work, the surface scanning method is applied through the use of an EMC Scanner, which is responsible for moving a near-field probe over the surface of the device to be analyzed. Different types of probes were used to evaluate the behavior of a printed circuit board of a singlestage commercial driver, used to power a LED tube lamp. The tests with the EMC Scanner are proposed in this work as a tool to support the tests already carried out during the validation of commercial luminaires. With the aid of this method, it is possible to locate more precisely the region that is emitting noise on a printed circuit board, in addition to better understanding its nature.